Application of Novel Non-Thermal Physical Technologies to Degrade Mycotoxins - Yousefi, Mohammad; Mohammadi, Masoud Aman; Khajavi, Maryam Zabihzadeh; Ehsani, Ali; Scholtz, Vladimír (Journal of fungi (Basel, Switzerland), 2021)
Mycotoxins cause adverse effects on human health. Therefore, it is of the utmost importance to confront them, particularly in agriculture and food systems. Non-thermal plasma, electron beam radiation, and pulsed light are possible novel non-thermal technologies offering promising results in degrading mycotoxins with potential for practical applications. In this paper, the available publications are reviewed-some of them report efficiency of more than 90%, sometimes almost 100%. The mechanisms of action, advantages, efficacy, limitations, and undesirable effects are reviewed and discussed. The first foretastes of plasma and electron beam application in the industry are in the developing stages, while pulsed light has not been employed in large-scale application yet.
Keywords: non-thermal plasma; pulsed light; electron beam; detoxification; filamentous fungi